2006
DOI: 10.1038/sj.hdy.6800904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and evolutionary biology of alternative splicing: how changing the mix of alternative transcripts affects phenotypic plasticity and reaction norms

Abstract: Alternative splicing (AS) of pre-messenger RNA is a common phenomenon that creates different transcripts from a single gene, and these alternative transcripts affect phenotypes. The majority of AS research has examined tissue and developmental specificity of expression of particular AS transcripts, how this specificity affects cell function, and how aberrant AS is related to disease. Few studies have examined quantitative between-individual variation in AS within a cell or tissue type, or in relation to phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 74 publications
1
58
0
Order By: Relevance
“…The scale in A-C is the percentage fraction of the shorter isoform relative to the total of both isoforms: [short isoform/(short isoform 1 long isoform)] 3 100. The numerical values for the population means and standard deviations are given in Table 2. control point for tissue-specific phenotype determination and homeostasis (Marden 2006). Four strategies may prove valuable in confirming this hypothesis in future experiments.…”
Section: Discussionmentioning
confidence: 83%
“…The scale in A-C is the percentage fraction of the shorter isoform relative to the total of both isoforms: [short isoform/(short isoform 1 long isoform)] 3 100. The numerical values for the population means and standard deviations are given in Table 2. control point for tissue-specific phenotype determination and homeostasis (Marden 2006). Four strategies may prove valuable in confirming this hypothesis in future experiments.…”
Section: Discussionmentioning
confidence: 83%
“…27 In this regard, in previous studies in T. infestans, we demonstrated that the GPDH isoforms are not distributed equally in space or time. It was determined that expression is related to insect tissue or development stage and the pattern of expression differs between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing realization that splicing efficiency is a significant contributor to phenotypic variability (Marden, 2008), and the contribution of splicing to phenotype has become particularly apparent through its impact on modifying the severity of human disease (Nissim-Rafinia and Kerem, 2002) and its contribution to disease susceptibility (Wang and Cooper, 2007). Indeed, a key factor in the motivation for the present study was the recent positional cloning of the first sarcoidosis (a polygenic autoimmune disorder of the lungs (Valentonyte et al, 2005)) disease gene, namely BTNL2.…”
Section: Disease Relevance Of Allele-dependent Splicingmentioning
confidence: 99%